2017
DOI: 10.1080/00224499.2017.1317709
|View full text |Cite
|
Sign up to set email alerts
|

Till Porn Do Us Part? A Longitudinal Examination of Pornography Use and Divorce

Abstract: As pornography use becomes more commonplace in the United States, and increasingly so among younger cohorts, a growing literature is considering its potential connection to key social and cultural institutions. The current study examined the relationship between pornography use and one such institution: marriage. We drew on three-wave longitudinal data from 2006 to 2014 General Social Survey panel studies to determine whether married Americans' pornography use predicted their likelihood of divorce over time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 47 publications
2
35
1
2
Order By: Relevance
“…Despite these limitations, which we discuss in greater detail below, because the survey question has been consistent over this time period it allows us to track trends in pornography viewership across different groups of interest. This outcome has also been widely used in previous studies of pornography consumption over time (Doran & Price, 2014;Patterson & Price, 2012;Perry & Schleifer, 2017;Price et al, 2016;Regnerus, Gordon, & Price, 2016;Wright, 2013;Wright et al, 2013), and thus, is profitably used here to address our research questions. Key Predictors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, which we discuss in greater detail below, because the survey question has been consistent over this time period it allows us to track trends in pornography viewership across different groups of interest. This outcome has also been widely used in previous studies of pornography consumption over time (Doran & Price, 2014;Patterson & Price, 2012;Perry & Schleifer, 2017;Price et al, 2016;Regnerus, Gordon, & Price, 2016;Wright, 2013;Wright et al, 2013), and thus, is profitably used here to address our research questions. Key Predictors.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, for religious commitment, we use a dichotomous measure of religious service attendance, coded 1 = monthly attendance, 0 = less than monthly (see Patterson and Price 2012; Voas and Chaves 2016 for similar coding). While we acknowledge that "religious commitment" is a multidimensional construct, worship attendance is often used as a reliable measure of "religiosity" (e.g., Doran & Price, 2014;Patterson & Price, 2012;Perry & Schleifer, 2017;Wright, 2013;Wright et al, 2013) and our use of this dichotomized measure allows us to observe discrete interactive patterns between race and pornography viewership across time that are considerably more interpretable than using a full range of attendance. Additionally, while the GSS includes other measures of religious commitment such as prayer and self-rated religiosity, only religious service attendance has been asked since 1973 and thus allows us to make use of all available GSS survey waves that ask about pornography use.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these limitations, which we discuss in greater detail below, because the survey question has been consistent over this time period it allows us to track trends in pornography viewership across different groups of interest. This outcome has also been widely used in previous studies of pornography consumption over time (Doran & Price, 2014;Patterson & Price, 2012;Perry & Schleifer, 2017;Price et al, 2016;Regnerus, Gordon, & Price, 2016;Wright, 2013;Wright et al, 2013), and thus, is profitably used here to address our research questions.…”
Section: Theorizing the Link Between Race Pornography Viewership Anmentioning
confidence: 99%
“…is a multidimensional construct, worship attendance is often used as a reliable measure of "religiosity" (e.g., Doran & Price, 2014;Patterson & Price, 2012;Perry & Schleifer, 2017;Wright, 2013;Wright et al, 2013) and our use of this dichotomized measure allows us to observe discrete interactive patterns between race and pornography viewership across time that are considerably more interpretable than using a full range of attendance. Additionally, while the GSS includes other measures of religious commitment such as prayer and self-rated religiosity, only religious service attendance has been asked since 1973 and thus allows us to make use of all available GSS survey waves that ask about pornography use.…”
Section: Theorizing the Link Between Race Pornography Viewership Anmentioning
confidence: 99%
“…Focusing primarily on religious service attendance as an indicator of religious commitment, some studies have found a non-significant relationship between attendance and divorce (Perry and Schleifer 2018;Vaaler et al 2009), while most others find the two factors to be significantly correlated (Amato and Rogers 1997;Brown et al 2008;Bulanda and Brown 2007;Clydesdale 1997;Massoglia et al 2011;Perry 2018;Sweezy and Tiefenthaler 1996;Wilcox 2004;Wilcox and Wolfinger 2016). Importantly, the association could be bi-directional due to the religious stigma that divorced Americans often face in religious contexts.…”
Section: Religion and Divorce In The United Statesmentioning
confidence: 99%